The Implementation of Annotated Bibliography Writing to Improve Research-Based Writing Skills of English Education Students - Muhammad Fauzi; Kotangenia Al-Farobi; Nurhaliza Rahmalia Budiman; Alek; Didin Nuruddin Hidayat (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
In the study, the implementation of annotated bibliography writing is explored as the educational method for improving research writing skills for students in English Education courses. Writing based on research is perceived as one of the most difficult aspects for EFL learners, especially when it comes to source evaluation, gathering new knowledge, and creating well-structured research arguments in academic writing. In the study, which employed the methodological framework that included students’ work on their own annotated bibliography analyses and interviews, it was found that research writing skills can be improved for students using the method of annotated bibliography writing as they gain abilities to successfully sum up research sources, assess their applicability and credibility, and combine ideas for research arguments. However, several factors, such as their limited capacity to understand complex research sources, produce appropriate research parodies, assess research methods, and combine sources for analytical arguments, worked against EFL learners, resulting in the production of research arguments in descriptive mode instead of using analysis.